Analisis Perbandingan Curah Hujan dan Debit Banjir di Das Citanduy Hulu Bendungan Leuwikeris - Sulwan Permana; Bambang Haidar Dwiyanto (Institut Teknologi Garut, 2023)
The Citanduy River, which is located in the East Priangan Region in West Java Province, recently during the rainy season, very high rainfall, long duration of rain, and uneven distribution of rain have caused flooding problems in several places, especially in the Tasikmalaya Regency, Ciamis, Banjar City, and Pangandaran Regency. Floods and landslides often occur in the upper reaches of the river, such as in the Tanjungsari area, Sukaresik District. Meanwhile, downstream, residents experienced flooding caused by the overflow of the Citanduy River, such as in the Sindangreja, Wanareja, Lakbok and surrounding areas. This study aims to obtain a comparative value of rainfall intensity in the upstream Citanduy watershed area to the Leuwikeris Dam using the Talbot, Sherman, and Ishiguro method, while the flood discharge uses the Nakayasu method. Based on the results of the comparative analysis of rainfall intensity calculations, the Ishiguro method is the most effective method used in calculating rainfall intensity with a value of 938.82 mm/hour in 2008-2014 and in 2015-2021 of 1126.74 mm/hour . Comparison of flood discharge for a return period of 2 years obtained results of 193.94 m3/second in 2008-2014 and in 2015-2021 obtained results of 232.77 m3/second, so from the results of calculating the comparison of flood discharges it can be concluded that the flood discharge in 2015-2021 is greater than the flood discharge in 2008-2014.